2012
DOI: 10.1186/1556-276x-7-576
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polysaccharide-maghemite composite nanoparticles and their antibacterial properties

Abstract: The aim of this study was to obtain saccharide (dextran and sucrose)-coated maghemite nanoparticles with antibacterial activity. The polysaccharide-coated maghemite nanoparticles were synthesized by an adapted coprecipitation method. X-ray diffraction (XRD) studies demonstrate that the obtained polysaccharide-coated maghemite nanoparticles can be indexed into the spinel cubic lattice with a lattice parameter of 8.35 Å. The refinement of XRD spectra indicated that no other phases except the maghemite are detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Dextran and sucrose coated MNPs (with diameter of 5.8 and 7.3 nm respectively) showed good inhibition against E. coli ATCC 25922 strain, especially at concentrations between 0.01-0.625 mg/mL [41]. This study also revealed that dextran is more effective as a coating medium regarding bactericidal activity compared to sucrose.…”
Section: Escherichia Colimentioning
confidence: 56%
See 1 more Smart Citation
“…Dextran and sucrose coated MNPs (with diameter of 5.8 and 7.3 nm respectively) showed good inhibition against E. coli ATCC 25922 strain, especially at concentrations between 0.01-0.625 mg/mL [41]. This study also revealed that dextran is more effective as a coating medium regarding bactericidal activity compared to sucrose.…”
Section: Escherichia Colimentioning
confidence: 56%
“…Other recent study reports the modulation of C. krusei infections by MNPs [18]. This modulation is dependent by the surface of MNPs and the authors pointed out that microbial interactions are influenced by interfacial forces, such as the electrostatic field, that plays a significant role on the interaction between MNPs and microbial surfaces [41].…”
Section: Candida Kruseimentioning
confidence: 96%
“…The amount of iron was determined using potassium dichromate (K 2 Cr 2 O 7 ). The Fe 2+ was titrated potentiometrically in agreement with previous studies [24]. After the last separation by centrifugation, the particles were dispersed into dextran (30% w/v).…”
Section: Methodsmentioning
confidence: 84%
“…The preparation of phase pure iron oxide or oxyhydroxide is a challenging task as their formation depends on various parameters such as concentration of iron starting material, pH and temperature of the solution. Previous attempts to prepare phase pure iron oxides or oxyhydroxides has resulted in the formation of product(s) such as maghemite (g-Fe 2 O 3 ) [21,22], lepidocrocite (g-FeOOH) [23], goethite (a-FeOOH) [24e26], akaganeite (b-FeOOH) [27], magnetite (Fe 3 O 4 ) [28,29] and hematite(a-…”
Section: Introductionmentioning
confidence: 99%